Towards Professionalism in Music: Self-assessed Learning Strategies of Conservatory Music Students - Esa Virkkula (University of Ljubljana, 2017)
One of the current spearhead projects in Finnish education is learning to learn. Learning strategies have been examined from a variety of perspectives. They are policies that either promote or hinder learning. They are any behaviours or thoughts that facilitate encoding in such a way that knowledge integration and retrieval are enhanced. Strategies can be practiced and learnt. Direct and indirect learning strategies formed the model of defining music students’ self-assessed learning habits in this research. The strategies dealt with here are memory, cognitive, compensation, metacognitive, affective and social strategies. Critical thinking strategies as well as deep and surface learning strategies were also observed. In this paper, a theoretical background and methodological solutions will first be presented. A significant finding comes from cross-professional collaboration of students, teachers, and professionals during the research period: it enhanced the use of strategies. Another finding, the profitable use of the workshop method, can be adopted by other fields of learning and make processes flexible and fruitful.